The Role of Sperm Centrioles in Human Reproduction – The Known and the Unknown - Avidor-Reiss, Tomer; Mazur, Matthew; Fishman, Emily L.; Sindhwani, Puneet (Frontiers in Cell and Developmental Biology, 2019)
Each human spermatozoon contains two remodeled centrioles that it contributes to the zygote. There, they reconstitute a centrosome that assembles the sperm aster and participates in pronuclei migration and cleavage. Thus, centriole abnormalities may be a cause of male factor infertility and failure to carry pregnancy to term. However, the precise mechanisms by which sperm centrioles contribute to embryonic development in humans is still unclear - making the search for a link between centriole abnormalities and impaired male fecundity particularly difficult. Most previous investigations into the role of centrioles during fertilization have been completed in animal models, which provide only limited information that can be translated to humans. Here, we review studies that examine the role of the sperm centrioles in the early embryo, with particular emphasis on humans. Available literature includes case studies and case-control studies, with a few retrospective and no prospective studies reported. This literature has provided some insight into morphological characteristics of sperm centrioles in the zygote and has allowed identification of some centriole abnormalities in rare cases. Many of these studies suggest centriole involvement based on phenotypes of the embryo with only indirect evidence for centriole abnormality. Overall, these studies suggest that centriole abnormalities are present in some cases of sperm with asthenoteratozoospermia and unexplained infertility. Yet, most previously published studies have been restricted by use of laborious techniques like electron microscopy and limited availability of centriolar markers, resulting in small scale studies and a lack solid causational evidence. With recent progress in sperm centriole biology, such as the identification of the unique composition of sperm centrioles and discovery of the atypical centriole, it is now possible to start to fill the gaps in sperm centriole epidemiology and identify the etiology of sperm centriole dysfunction in humans.